2016
DOI: 10.1002/ase.1604
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an online three‐dimensional interactive resource for undergraduate neuroanatomy education

Abstract: Neuroanatomy is one of the most challenging subjects in anatomy, and novice students often experience difficulty grasping the complex three-dimensional (3D) spatial relationships. This study evaluated a 3D neuroanatomy e-learning module, as well as the relationship between spatial abilities and students' knowledge in neuroanatomy. The study's cross-over design divided the participants into two groups, each starting with tests for anatomy knowledge and spatial ability, followed by access to either the 3D online… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
92
0
19

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(115 citation statements)
references
References 53 publications
4
92
0
19
Order By: Relevance
“…1 Based on both the quantitative results and the satisfaction survey results, there is evidence that virtual-reality technology may provide an effective supplemental tool for learning neuroanatomy by decreasing neurophobia and increasing knowledge retention. Our results are in concordance with those of studies using virtual 2-and 3-dimensional models [25][26][27] and suggest that learning complex, 3-dimensional relations between neural structures is facilitated by training in a 3-dimensional virtual-reality environment. Our findings corroborate those of Armstrong and colleagues 28 showing qualitative benefits of immersive and interactive virtual-reality compared to other methods and extends them into the quantitative domain.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…1 Based on both the quantitative results and the satisfaction survey results, there is evidence that virtual-reality technology may provide an effective supplemental tool for learning neuroanatomy by decreasing neurophobia and increasing knowledge retention. Our results are in concordance with those of studies using virtual 2-and 3-dimensional models [25][26][27] and suggest that learning complex, 3-dimensional relations between neural structures is facilitated by training in a 3-dimensional virtual-reality environment. Our findings corroborate those of Armstrong and colleagues 28 showing qualitative benefits of immersive and interactive virtual-reality compared to other methods and extends them into the quantitative domain.…”
Section: Discussionsupporting
confidence: 82%
“…3 Time constraints and desire for cost-effectiveness have prompted medical schools to reduce anatomy and laboratory teaching time with human cadaveric specimens, [3][4][5][6] the main supplementation material being textbooks and 2-dimensional images. 3,7 These restrictions may influence a person's ability to translate 2-dimensional to 3-dimensional spatial relations, as it requires the student to perform complex cognitive reconstructions, 8,9 potentially impairing neuroanatomical learning. A previous study showed a dramatic decrease in neuroanatomy recall among graduating medical students, 10 and other studies indicated that medical graduates' overall anatomic competence did not meet safe practising level.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Incorporating three‐dimensional (3D) elements in anatomy teaching has been shown to favor spatial understanding and visualization of the relationship between different structures (Allen et al, ). Furthermore, recent advances in the utilization of 3D technology such as cone‐beam computerized tomography in dental practice requires dental students and clinicians to manoeuvre and recognize 3D tooth images (Bell et al, ; Hajeer et al, ; Benavides et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Following a student-centered approach, online instructional materials (e.g., videos) are made to be as interactive as possible so that the learner controls the flow of the course [21][22][23].…”
Section: Benefits Of Online Supplementary Instructionmentioning
confidence: 99%